2008
DOI: 10.4103/0972-0707.44053
|View full text |Cite
|
Sign up to set email alerts
|

Fiber optic backscatter spectroscopic sensor to monitor enamel demineralization and remineralizationin vitro

Abstract: In this study, a Fiber Optic Backscatter Spectroscopic Sensor (FOBSS) is used to monitor demineralization and remineralization induced changes in the enamel. A bifurcated fiber optic backscatter probe connected to a visible light source and a high resolution spectrophotometer was used to acquire the backscatter light spectrum from the tooth surface. The experiments were conducted in two parts. In Part 1, experiments were carried out using fiber optic backscatter spectroscopy on (1) sound enamel and dentine sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…Thomas et al showed a gradual increase of the diffuse reflectance during tooth erosion, 17 though the sensitivity of the signal to erosive changes was poor. Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies. 19,20 Particularly, sharp decay of the specular reflection was observed already in the early stages of enamel erosion in vitro, while the less pronounced increase of the diffuse reflection intensity was measured, which correlated well with the results of Thomas et al 17 Further investigation revealed a strong correlation between the decrease of the specular reflection and continuous surface roughening.…”
Section: Introductionmentioning
confidence: 99%
“…Thomas et al showed a gradual increase of the diffuse reflectance during tooth erosion, 17 though the sensitivity of the signal to erosive changes was poor. Linear decrease and increase of the backscattered light intensity during demineralization and remineralization processes were reported by Kishen et al 18 Change of the specular and diffuse reflection intensities during erosion progression was investigated in our previous in vitro studies. 19,20 Particularly, sharp decay of the specular reflection was observed already in the early stages of enamel erosion in vitro, while the less pronounced increase of the diffuse reflection intensity was measured, which correlated well with the results of Thomas et al 17 Further investigation revealed a strong correlation between the decrease of the specular reflection and continuous surface roughening.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a fiber optic backscatter spectroscopic sensor was successfully applied to monitor in vitro enamel demineralization and remineralization. 16 Thomas et al 10 used another fiber optic setup to monitor change of the diffuse reflection spectra after demineralization of enamel and dentine samples. However, the authors concluded that the diffuse reflection signal had a low sensitivity for enamel etching.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional microscopy suffers from the problem as light scattering, namely multiple scattering from objects that are out of focus within the illuminated region prevents imaging deep within a sample. Further, if care is not taken, optical microscopy can lead to the observation of certain artifacts which in turn leads to incorrect physical interpretation of the system in question [3,9].…”
Section: Discussionmentioning
confidence: 99%
“…Confocal laser scanning microscopy is a powerful imaging technique based upon optical behavior of light within specimens. Generally, confocal analysis features excita-tion (such as fluorescence) although emission detection is also possible [3]. The optical property of this technique helps in the detection of carious and non-carious lesions of the tooth [4].…”
Section: Introductionmentioning
confidence: 99%